PROJECT-BASED LEARNING: PROMOTING EFL LEARNERS’ WRITING SKILLS - Aghayani, Behnam; Hajmohammadi, Elmira (LLT Journal: A Journal on Language and Language Teaching, 2019)
The present study sought to investigate the effect of project-based learning on EFL learners’ writing skill. To reach this goal, from the population of 70 EFL learners taking EFL courses at a language institute in Iran, two homogenous groups, consisting of 28 males, were selected based on the random sampling method. While the control group with 14 learners was taught through traditional method, the experimental group consisting of 14 learners received instruction using project-based learning designed by Maftoon, Birjandi, and Ahmadi (2013). A pre-test was administered to both groups prior to the treatment. Then, after the treatment, which was lasted for ten sessions and held during two months, the learners in both group were required to write on the new topic in which it was regarded as the writing post-test. The analysis of the obtained data revealed that project-based learning had significant effect on the learners’ writing ability. Moreover, the findings showed that project-based learning approach does aid learners to enhance and promote their writing ability in a collaborative environment. DOI: doi.org/10.24071/llt.2019.220108